Ripening of musa sapientum c.v lakatan using madre de cacao (Gliricidia sepium as biothylene source. - Imperial, Kubail Bagac (2000.)
This study was conducted to characterize ripening of Gliricidia-treated fruits and to determine the minimum concentration necessary to promote ripening., Mature green 'Lakatan' fingers were incubated with 0 percent-10 percent (w/w) chopped or unchopped Gliricida leaves. The ripening was evaluated based on the following: peel color development, visual quality rating, percent weight loss, shelf life, physico-chemical characteristics, and sensory attributes. Gliricida leaves can indeed promote ripening . Chopped leaves at 5 percent - 10 percent and 7.5 percent - 10 percent unchopped were effective to accelerate ripening. Therefore, the minimum concentration if applied chopped is 15 percent and 7.5 percent if not chopped.
Thesis (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines in the Visayas, Iloilo City.
Keywords: Musa Sapientum c.v.; Lakatan